Persistent immune-related adverse events after cessation of checkpoint inhibitor therapy: Prevalence and impact on patients' health-related quality of life. (November 2022) - Schulz, Thomas U.; Zierold, Sarah; Sachse, Michael M.; Pesch, Giulia; Tomsitz, Dirk; Schilbach, Katharina; Kähler, Katharina C.; French, Lars E.; Heinzerling, Lucie
Abstract: Background: Immune checkpoint inhibitors (ICIs) may induce persistent immune-related adverse events (irAEs). We investigated persistent irAEs and implications on patients' lives compared to non-ICI-induced autoimmune diseases (AIs). Methods: The multicentre, cross-sectional study comprised 200 patients with cancer ≥12 weeks after ICI cessation (ICI-patients) and 2705 patients with AIs (AI-patients), recruited in German outpatient clinics and support groups. The prevalence of persistent irAEs subdivided in long-term (12 weeks to <12 months) and chronic irAEs (≥12 months) since ICI discontinuation, health-related quality of life (HRQoL) using the EuroQol 5D-5L (EQ-Index/VAS score), and burden of autoimmune symptoms and respective therapies were assessed. Results: Long-term/chronic irAEs occurred in 51.9%/35.5% of outpatient ICI-patients, including arthralgia (16.7%/16.1%), myalgia (13.0%/14.0%), hypothyroidism (11.1%/10.8%), xerostomia (7.4%/8.6%), vitiligo (13.0%/7.5%) and hypophysitis (9.3%/7.5%). ICI-patients with long-term/chronic irAEs reported clinically significantly reduced HRQoL compared to ICI-patients without long-term/chronic irAEs (EQ-Index score: 0.767/0.752 versus 0.920/0.923, p < 0.001/0.001; EQ-VAS score: 52.2/52.0 versus 63.6/74.7, p =/< 0.040/0.001). Multiple linear regression analyses confirmed clinically significant reductions in HRQoL scores by chronic irAEs (EQ-Index/VAS score: −0.163/−23.4, p < 0.001/0.001). HRQoL, burden of autoimmune symptoms and burden of respective therapies in ICI-patients with chronic irAEs were similar to AI-patients with non-exacerbated AIs. Patients with chronic irAEs felt inadequately informed about side-effects compared to patients without chronic irAEs (p < 0.001). Conclusion: Persistent irAEs impose a significant burden on patients after ICI cessation. Especially in early tumour stages, risk-benefit ratios must be carefully evaluated, and patients need to be informed about potential long-term sequelae. Graphical abstract: Image 1 Highlights: Up to 35.5% of patients with cancer have chronic immune-related adverse events (irAEs) ≥1 year since immune checkpoint inhibitor cessation. Chronic irAEs drastically reduce health-related quality of life (HRQoL) after immune checkpoint inhibitor cessation. Cancer patients without chronic irAEs show similar HRQoL to the normal population. Chronic irAEs have similar impacts on HRQoL as non-exacerbated autoimmune diseases. Patients with chronic irAEs felt inadequately informed about long-term sequelae.